Scientific Nursing Production about Alzheimer's Disease: A Bibliometric Study - , Dayara de Nazaré Rosa de Carvalho; , Thanaira Aicha Fernandes Maciel; , Bárbara Leticia Corrêa Gomes; , Amanda Ourqiues de Gouveia; , Dandara de Fátima Ribeiro Bendelaque; , Kelly de Cássia Peixoto de Oliveira Silveira; , Viviane Ferraz Ferreira de Aguiar; , Fabiana de Souza Orlandi; , Camila Almeida Bonfim; , Ivonete Vieira Pereira Peixoto (Archives of Current Research International, 2024)
Aims: to analyze and map the international scientific production of Nursing on Alzheimer's Disease, in the historical series from January 2016 to November 2021. Methodology: This is a study of a basic nature, with a mixed approach and under the light of procedures methodological, configures itself as research of the Bibliometric type. Data collection took place in July 2021 through institutional online access to the CAPES Journal Portal, in the Scopus (Elsevier) database, using the combination of the following MESHs: "Alzheimer's disease", "Elderly", "Very Old" and “Nursing”, all mediated by the Boolean operators “AND” and/or “OR”. The final sampling resulted in 189 publications. Results: n=189 publications were identified, distributed in n=66 journals, divided into 30 countries. It was evidenced that the year 2016 has the highest number of publications with n=44 (23.28%), followed by the year 2017 with n=42 (22.22%) articles and 2018 with n=38 (20.11) %) articles, these being the years with the highest number of publications. From the analysis of the included studies, it was observed that the publications that made up this Bibliometric review addressed 4 large distinct thematic groups: 1) Difficulties encountered by family caregivers with elderly people with Alzheimer's disease; 2) Nursing in Home Care for the Elderly with Alzheimer's Disease in Palliative Care; 3) Behaviors Observed in Elderly People with Severe Dementia and 4) Quality of Life in Elderly People with Cognitive Disabilities. Conclusion: Despite the few publications in the database, it is observed that the publications are at a high level of quality when we look at the evaluation metrics of the selected studies. It can be seen that the main research centers on the subject are in countries such as France, Japan, the United Kingdom and the Netherlands. Furthermore, the study demonstrated the various gaps that need to be addressed and deepened on the subject that require scientific investigation.